Modern Challenges of Military Logistics: Analysis of the Supply of the Armed Forces of Ukraine in the Conditions of War With Russia - Burdeina, Nadiya; Fedchenko, Oleksandr; Vensyuk, Andriy (Social Development and Security, 2025)
Purpose: is to study the current challenges faced by the Ukrainian army in the field of logistics, in particular, issues related to supply, transportation, storage, and distribution of material and technical resources. Method: theoretical-analytical method. Findings: The study establishes that the current state of logistical operations in the Armed Forces of Ukraine defines key challenges and problems related to resource management, coordination, and efficiency. Based on the analysis, possible ways to improve logistical processes and enhance the combat readiness of the Ukrainian troops in the conditions of modern warfare are considered. Theoretical implications: It allows for a systematic study of key aspects of logistics, focused on several main areas, which will contribute to improving the logistical support of the Armed Forces of Ukraine in the conditions of the war with Russia. Practical implications: The results of the analysis can be useful for improving the coordination and efficiency of logistics operations. It is recommended to implement centralized management, i.e. the creation of a single command center that coordinates all logistics processes, including supply, transportation, storage and distribution of material resources. Paper type: theoretical.